PANEL DATA ANALYSIS OF THE IMPACT OF AGRICULTURAL INDICATORS ON ECONOMIC DEVELOPMENT ASPECTS: THE EXPERIENCE FROM THE BRICS COUNTRIES - Madžar, Lidija; Đekić, Ivan; Đurić, Zorica (Economics of Agriculture, 2025)
The aim of this paper is to empirically assess the influence of the most significant agricultural measures on basic economic indicators in original BRICS countries (Brazil, Russia, India, China and South Africa), as well as to offer reasonable explanations for the nature of the established relations. For this purpose, two models were built: a) The Period Random Effects Model that traces their influence on GDP growth rate, and b) Two-way Random Effects Model that assesses their influence on Average income in BRICS nations. The paper determined mostly negative and statistically significant relations between mere agricultural measures and economic indicators, pointing to the conclusion that these countries are burdened by problems of law agricultural productivity, poor technological progress and low value added in their agriculture, as well as to the need for the implementation of more serious institutional, land, production, education, infrastructural and other fields of reforms in BRICS.